Antibody Detection to Feline Immunodeficiency virus (FIV) in stray cats in Ahvaz, southwestern Iran - Mosallanejad, B. (Archives of Razi Institute, 2010)
The present study was performed to determine the prevalence of FIV in stray cat's population of Ahvaz different area. Serum samples were collected from 90 cats from 2005 to 2007. The studied cats were divided into two age groups (<3 years and >3 years) and based on clinical signs (such as lymphadenopathy, periodontal diseases, gingivitis, abscess and cashecsi) into two groups also. The results were analyzed using Fischer's exact test and Chi-square analysis. Prevalence to FIV antibodies in these cats was 15.55% (14 of 90) by means of ELISA Test Kit, indicating that this virus is present in the ecosystem. The infection had more prevalence in cats above 3 years (78.6%; 11 of 14) compared with cats less than 3 years (21.4%; 3 of 14). Statistical analysis showed significant difference between different age groups (P<0.05). Prevalence of infection was 17.31% (9 of 52) in males and 13.16% (5 of 38) in females, nevertheless the infection was not significant between different genus (p>0.05). Three out of 12 cases (25%) which had clinical signs and 11 out of 78 cases (14.1%) which hadn’t clinical signs were seropositive. There was no significant difference between the two groups also (P>0.05). This study showed that FIV exist among cat's population of Ahvaz area and separation of companion and stray cats is very important for prevention of disease transmission to companion cats.